2014
DOI: 10.1177/0023830913513206
|View full text |Cite
|
Sign up to set email alerts
|

The Early Phase of /ɹ/ Production Development in Adult Japanese Learners of English

Abstract: Although previous research indicates that Japanese speakers' second-language (L2) perception and production of English /ɹ/ may improve with increased L2 experience, relatively little is known about the fine phonetic details of their /ɹ/ productions, especially during the early phase of L2 speech learning. This cross-sectional study examined acoustic properties of word-initial /ɹ/ from 60 Japanese learners with a length of residence (LOR) between one month and one year in Canada. Their performance was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 58 publications
(91 reference statements)
1
24
0
Order By: Relevance
“…Focusing on Chinese learners of English in classroom settings, Rau, Chang, and Tarone () showed that English /ɵ/ was mispronounced more frequently in a picture description task than in word and sentence reading tasks. Although inexperienced Japanese learners’ English /r/ pronunciation proficiency (length of residence <1 year) was comparable across different task conditions (Saito & Munro, ), more experienced Japanese learners (length of residence >1 year) produced English /r/ more accurately when their speech was elicited from word and sentence reading tasks than from picture description tasks (Saito & Brajot, ). The researchers interpreted this task effect in performance (controlled > spontaneous) as arising from the increased demands on linguistic processing due to the lack of substantial planning time for the picture description tasks compared to the more controlled reading tasks (for similar results concerning consonant clusters, see Lin, ).…”
Section: Different Types Of L2 Pronunciation Instruction and Resultinmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on Chinese learners of English in classroom settings, Rau, Chang, and Tarone () showed that English /ɵ/ was mispronounced more frequently in a picture description task than in word and sentence reading tasks. Although inexperienced Japanese learners’ English /r/ pronunciation proficiency (length of residence <1 year) was comparable across different task conditions (Saito & Munro, ), more experienced Japanese learners (length of residence >1 year) produced English /r/ more accurately when their speech was elicited from word and sentence reading tasks than from picture description tasks (Saito & Brajot, ). The researchers interpreted this task effect in performance (controlled > spontaneous) as arising from the increased demands on linguistic processing due to the lack of substantial planning time for the picture description tasks compared to the more controlled reading tasks (for similar results concerning consonant clusters, see Lin, ).…”
Section: Different Types Of L2 Pronunciation Instruction and Resultinmentioning
confidence: 99%
“…While making impressionistic, global judgments of spontaneous speech, raters have been found to take into account both phonological and nonphonological variables, including lexical, pragmatic, and contextual information (Broersma & Cutler, ). Raters’ evaluations are likely influenced by their previous listening experience or familiarity with particular foreign accents (e.g., Bent & Bradlow, ), and they use different acoustic information to analyze the same speech target according to different rating constructs (accuracy vs. intelligibility) and speaker proficiency (e.g., Saito, ; Saito & Munro, ).…”
Section: Discussionmentioning
confidence: 99%
“…L2 speech-the focus of the present study-is a multifaceted phenomenon comprising a wide range of different linguistic skills. According to previous literature on naturalistic L2 speech learning, learners tend to show a great deal of improvement within a short period of immersion (e.g., first 3 to 4 months of stay) in terms of global dimensions of speech, such as comprehensibility and accentedness (e.g., Derwing, Munro, & Thomson, 2008), as well as its temporal (e.g., Segalowitz & Freed, 2004), segmental (Saito & Munro, 2014), and lexicogrammatical (Mora & Valls-Ferrer, 2012) aspects as long as learners use the L2 as their main language of communication in various social settings (for a review of experience effects in naturalistic L2 development, see Saito, 2015).…”
Section: Experience L2 Speech Learning and Individual Differencesmentioning
confidence: 99%
“…Although L2 pronunciation performance has traditionally been measured via controlled speech measures, where L2 learners fully focus on the correct pronunciation of target sounds (e.g., word and sentence reading), certain researchers have adopted spontaneous speech measures (e.g., picture description, monologue, oral interview tasks: Piske, Flege, MacKay, & Meador, 2011). To tap into the participants' controlled and spontaneous processing abilities of English /ɹ/ production, three tasks elaborated in the author's precursor research (Saito, 2013a;Saito & Brajot, 2013;Saito & Munro, 2014)-word reading (WR), sentence reading (SR), and timed picture description (TPD)-were used in the current study.…”
Section: Speaking Taskmentioning
confidence: 99%
“…This in turn suggests that the potentially different amount of task-specific awareness during their completion of WR, SR and TPD did not significantly influence their English /ɹ/ performance at least in the context of the current study with N = 40 English-as-a-Foreign-Language students (cf. for clear task effects on 100+ experienced Japanese learners' English /ɹ/ pronunciation and the validity of the method per se, seeSaito, 2013a;Saito & Brajot, 2013;Saito & Munro, 2014).…”
mentioning
confidence: 99%